Adaptation Strategies of Islamic Boarding Schools in Lombok in Facing the Digital Age - Murdianto, Murdianto (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2021)
This research examines the adaptation strategies implemented by pesantren in Lombok to face the challenges of the digital era. Amid increasingly massive digitalization, pesantren, as traditional Islamic educational institutions, are required to maintain pesantren values while adapting to technological developments. Through a qualitative approach with a case study method on five pesantren on Lombok Island, this research identifies various adaptation strategies to address these challenges. The results showed that pesantren in Lombok have implemented several adaptive strategies, including (1) integration of digital technology in the learning system, (2) curriculum development that combines religious knowledge with digital skills, (3) increasing the digital competence of ustadz and santri, and (4) strengthening filters against the negative impact of digital technology. Despite facing various obstacles such as limited infrastructure and human resources, pesantren in Lombok have shown the ability to transform without losing their fundamental characteristics as Islamic educational institutions. These findings provide an overview of how traditional educational institutions can adapt to the changing times while maintaining their essential values.